Factors Affecting Contraceptive Behaviour Among Adolescents - Sutarmi; Siska Sibua; Lina Darmayanti Bainuan; Widya Astuti; Yoanita Hijriyati (Sustainable Applied Modification Evidence Community (SAMEC), 2025)
Teenage pregnancy is a significant public health problem, especially in developing countries such as Indonesia. This study aimed to examine the effectiveness of school-based comprehensive sexuality education in reducing teenage pregnancy rates through improving knowledge, attitudes, and preventive behaviours. The method used was a quasi-experiment with a pretest-posttest control group design on 200 secondary school students in an area with high pregnancy rates. The UNESCO guideline-based comprehensive sexuality education intervention covered biological, emotional, social aspects, and decision-making skills delivered through active learning. Data were collected using a validated structured questionnaire and analysed using t-test and multiple linear regression. The results showed a significant increase in knowledge, attitude, and pregnancy prevention behaviour scores in the intervention group compared to the control (p < 0.001). The regression model revealed that knowledge and attitude were the main predictors of prevention behaviour with a contribution of 54.2%. These findings confirm that comprehensive sexuality education is effective in improving reproductive health literacy and shaping healthy and responsible sexual behaviour. Therefore, the main recommendation is to integrate this programme into the national curriculum and strengthen teacher training to support sustainable teenage pregnancy prevention.